Secondary headache attributed to exposure to or overuse of a substance. (April 2021) - Toom, Kati; Braschinsky, Mark; Obermann, Mark; Katsarava, Zara
Background: Secondary headaches attributed to exposure to or the overuse of a substance are classified under chapter eight in the International Classification of Headache Disorders 3rd edition. Three distinct sub-chapters consider: 1. Headache attributed to exposure to a substance, 2. Medication overuse headache, and 3. Headache attributed to substance withdrawal. Headache attributed to exposure to a substance refers to a headache with onset immediately or within hours after the exposure, while medication overuse headache is a headache occurring on 15 or more days per month that has developed as a consequence of regular usage of acute headache medication(s) for more than three consecutive months in a patient with a pre-existing primary headache disorder. The withdrawal of caffeine, oestrogen, and opioids is most often associated with the development of headache. Discussion: Despite the current headache classification, there is no certainty of a causal relationship between the use of any substance and the development of headache. Some substances are likely to provoke headache in patients that suffer from a primary headache disorder like migraine, tension-type headache or cluster headache, while others were described to cause headache even in people that generally do not get headaches. Toxic agents, such as carbon monoxide (CO) are difficult to investigate systematically, while other substances such as nitric oxide (NO) were specifically used to induce headache experimentally. If a patient with an underlying primary headache disorder develops a headache, in temporal relation to exposure to a substance, which is significantly worse than the usual headache it is considered secondary. This is even more the case if the headache phenotype is different from the usually experienced headache characteristics. Medication overuse headache is a well-described, distinct disease entity with only marginally understood pathophysiology and associated psychological factors. Managing medication overuse headache patients includes education, detoxification, prophylactic treatments and treating comorbidities, which is reflected in available guidelines. Viewing medication overuse headache as a separate entity helps clinicians and researchers better recognise, treat and study the disorder. Conclusion: Identification of substances that may cause or trigger secondary headache is important in order to educate patients and health care professionals about potential effects of these substances and prevent unnecessary suffering, as well as deterioration in quality of life. Treatment in case of medication overuse and other chronic headache should be decisive and effective.